Memorandum of Understanding between the James P. Grant School of Public Health (JSGSPH), BRAC University and The George Washington University School of Public Health and Health Services (2011) - James P. Grant School of Public Health (JSGSPH), BRAC University; The George Washington University (BRAC University and The Goerge Washington University, 2013)
This Memorandum of Understanding ("MoU") is entered into by James P. Grant School of Public Health, BRAC University, Dhaka, Bangladesh ("JPGSPH"), and The George Washington University, Washington, DC, USA ("GWU") on behalf of its unincorporated division, The George Washington University School of Public Health and Health Services ("SPHHS") and its Center for Global Health ("GWUlCGH").